The pricing implications of the oligopolistic securities lending market: A beneficial owner perspective - Zsuzsa R. Huszár; Zorka Simon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
In the last decade, central bank interventions, flights to safety, and the shift in derivatives clearing resulted in exceptionally high demand for high quality liquid assets, such as German treasuries, in the securities lending market besides the traditional repo market activities. Despite the high demand, the realizable securities lending income has remained economically negligible for most beneficial owners. We provide empirical evidence of pricing inefficiencies in the non-transparent, oligopolistic securities lending market for German treasuries from 2006 to 2015. Consistent with Duffie, Gârleanu and Pedersen (2005)'s theory, we find that the less connected market participants' interests are underrepresented, evident in the longer maturity segment, where lenders are more likely to be conservative passive investors, such as pension funds and insurance firms. The low price elasticity in this segment hinders these beneficial owners to fully capitalize on the additional income from securities lending, giving rise to important negative welfare implications.
urn:nbn:de:hebis:30:3-466823
Keywords: G12; G18; G21; G23; 330